THE EFFECT OF VIRTUAL REALITY ON COGNITIVE FUNCTIONS IN LADIES WITH DEMENTIA: LITERATURE REVIEW - Seran, Emeltriana Emilinda Aek; Haryanto, Joni; Ulfiana, Elida (Universitas Airlangga, 2021)
Introduction: The decline in cognitive function that occurs in the elderly with dementia will have an impact on decreasing daily physical and social activities in the elderly resulting in decreased quality of life for the elderly. One of the interventions that can be used to maintain cognitive function in the elderly is by using virtual reality. Purpose: The purpose of this study is to explain the effect of virtual reality on cognitive function in elderly people with dementia based on empirical studies in the last five years. Method: the process of searching for journals or articles using a database indexed by Scopus, ProQuest, and Science Direct using adequate keywords. The framework used for the review was PICOS and the inclusion criteria used were English-language journals with issues from 2015 to 2020. Data analysis and tabulation were carried out in articles or journals. Title, abstract, full text, and methodology are assessed to determine the eligibility of the article or journal. Results: 758's articles were identified, ten articles fit the research criteria. Virtual reality affects cognitive function where it can improve memory, attention, executive function and can increase the overall scale of the MoCA. The advantage over the use of virtual reality for the elderly with dementia is that it not only improves cognitive but also improves motor coordination, reduces behavioral and psychological symptoms, and can be used to detect cognitive impairments early. Conclusion: In carrying out cognitive rehabilitation programs in the elderly can use technology-based interventions by using virtual reality.